Short-Lived Radionuclides for the Assessment of Rapid Cardiovascular Drug Effects - Knapp, W. H.; Helus, F.; Tillmanns, H.; Elfner, R.; Ostertag, H.; Kübler, W. (Nuklearmedizin - NuclearMedicine, 1980)
Continuous monitoring of cardiac output and sequential studies of right ventricular ejection fraction and of fractional myocardial uptake of substances with high cell affinity can be realized using 13N (t1/2 = 9.6 min) and 81mKr (t1/2 = 13 sec). Thus, it is possible to measure rapid changes of absolute myocardial blood flow and of the inotropic state of the right heart myocardium. This is shown in patients who underwent interventions with Dipyridamole and with Dobutamine which produce a marked increase in myocardial blood flow or cardiac dynamics, respectively.